Comparative Effectiveness of Vonoprazan Dosing Strategies in Bismuth-Based Quadruple Therapy for Helicobacter pylori Eradication: A Prospective Non-inferiority Cohort Study - Yan, Lingling; Lin, Rong; Zhang, Yu; Xu, Shanjing; Zhou, Xianbin; Ma, Jiali; Fang, Lina (Turkish Journal of Gastroenterology, 2026)
Background/Aims: Vonoprazan 20 mg twice daily is effective for Helicobacter pylori (H.pylori) eradication, but studies on the efficacy of 20 mg once daily are limited. The efficacy, tolerability, and cost-effectiveness of bismuth-based quadruple therapy with vonoprazan 20 mg once daily were evaluated for H. pylori eradication. Materials and Methods: A prospective cohort study was conducted at TaiZhou Hospital of Zhejiang Province between January and September 2024. Participants were divided into 2 groups: low-dose vonoprazan (QD, 20 mg once daily) and standard-dose vonoprazan (BID, 20 mg twice daily). The remaining drugs (colloidal bismuth pectin, clarithromycin, and amoxicillin) were the same for both groups, with a treatment duration of 14 days. Urea breath tests were performed 6-8 weeks post treatment. Results: In the intention-to-treat analysis, eradication rates were 89.2% (91/102) in the QD group and 88.9% (88/99) in the BID group, with no significant difference (P = .941). In the per-protocol (PP) analysis, eradication rates were 92.2% (83/90) in the QD group and 95.2% (79/83) in the BID group, also without a significant difference (P = .426). The incidence of adverse events was 8.9% in the QD group and 12.0% in the BID group (P = .497), respectively. The cost-effectiveness ratios were 2.59 for the QD group and 3.96 for the BID group in the PP analysis, respectively. Conclusion: Vonoprazan 20 mg once daily showed comparable efficacy to twice-daily dosing as part of a bismuth-based quadruple regimen for H. pylori eradication, with better cost-effectiveness, making it a promising option, especially in resource-limited settings. Cite this article as: Yan L, Lin R, Zhang Y, et al. Comparative effectiveness of vonoprazan dosing strategies in bismuth-based quadruple therapy for Helicobacter pylori eradication: A prospective non-inferiority cohort study. Turk J Gastroenterol. Published online February 13, 2026. doi: 10.5152/tjg.2026.25645.